Conservation Subdivision: Design Phase – Patch Size and Shape of Conserved Open Spaces - Mark Hostetler; Hal Knowles (EDIS)
WEC275, a 5-page illustrated fact sheet by Mark Hostetler and Hal Knowles, III, focuses on conserving biodiversity of native species when land is subdivided. Includes additional resources. Published by the UF Department of Wildlife Conservation and Ecology, December 2009.